Aplikasi Automated Text Summarization (ATS) Pembuat Lead (Teras) Berita dengan Text to Speech (TTS) Menggunakan Algoritma TF-IDF dan Vector Space Model - Ni Komang Mika Karmila; Made Windu Antara Kesiman; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2013)
When reading the newspaper, people only tend to choose some news to be read. This is done because of the limited time which is had by the society. By reading the leads (the terrace) of the news, people can judge the whole content of the news. This phenomenon becomes a challenge for the journalists (news writers) to write an interesting leads that can attract the readers as much as possible. However, making a lead is not an easy thing. This study aimed to (1) design a lead maker application and (2) apply the lead maker application design. The method which was used in this research was development. The lead maker application has two main processes, namely the process of summarization by applying TF-IDF and Vector Space Model algorithm as well as the process of reading the summarize by utilizing MBROLA and the diphone database id1 which is generated by eSpeak. The product of this research was the lead maker application that can create and read a summary of a news article in Indonesian language, in .docx and .txt format. The testing result of the lead maker application showed that it run its function well in terms of functional and conceptual/ structural aspects. This application is implemented by using the Java programming language which is expected to ease the task of the journalists to make the news leads, especially in terms of processing time’s efficiency.